Anti-spastic effect induced by waggle needling correlates with KCC2-GABAA pathway in post-stroke spasticity rats. (17th April 2021) - Wang, Jun-Xiang; Ma, Liang-Xiao; Mu, Jie-Dan; Sun, Tian-Yi; Qian, Xu; Yu, Wen-Yan; Tian, Yuan; Zhang, Zhou
Graphical abstract: Highlights: Waggle needling at GB34 alleviates muscle tone and improves motor functions in post-stroke spasticity rats. Waggle needling shows superior neuroprotective effect over routine and placebo needling by reducing cerebral infarct volumes. Waggle needling enhances the expressions of KCC2 and GABAA γ2 which are decreased following an ischemic stroke. KCC2 antagonist blocks waggle needling-induced muscle tone alleviation and motor function improvements. Flexible application of suitable needling techniques for various diseases is of high value in clinical settings. Abstract: Although clinical efficacy of waggle needling has been confirmed, therapeutic mechanisms still remain poorly understood. Reduction of GABA was involved in the etiology of spasticity. Recently, accumulated evidences suggest that the inhibitory effect of GABA is determined by low intracellular chloride concentration, which is predominantly mediated by KCC2. This study was designed to investigate whether KCC2-GABAA pathway was involved in the mechanism underlying acupuncture intervention in rats with middle cerebral artery occlusion (MCAO). Three days after modeling, the rats received waggle needling, routine needling and placebo needling for 7 consecutive days. After treatment, the muscle spasticity, motor function and infarct volumes were tested. KCC2 and GABAA γ2 levels were detected via western blotting, RT-PCR and immunofluorescence. KCC2 antagonist and agonist were administered after the last intervention. We found that acupuncture, particularly waggle needling, could remarkably alleviate muscle spasticity, reverse motor deficits and reduce cerebral infraction in MCAO rats, possibly due to its effects on up-regulating expressions of KCC2 and GABAA γ2 in the cortical infarct regions. However, the effects were blocked by KCC2 antagonist. In summary, this study suggests that improvements in muscle spasticity and motor function induced by waggle needling correlates with the activation of KCC2-GABAA pathway.